2008
DOI: 10.4049/jimmunol.181.8.5748
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance without Clonal Expansion: Self-Antigen-Expressing B Cells Program Self-Reactive T Cells for Future Deletion

Abstract: 2), it was presumed that anti-IgD Abs targeted resting B cells, and due to a lack of costimulatory molecules, these B cells tolerized MBP-specific T cells. Similarly, it was shown that passive transfer of B cells expressing a myelin peptide prevented the induction of EAE (6 -8) or even EAE relapses (9). One explanation why B cells induce tolerance of naive but not memory T cells might be the need for expression of costimulatory molecules by the APC to activate naive T cells, specifically B7-1 and/or B7-2, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 47 publications
3
55
0
1
Order By: Relevance
“…There is clear evidence that B cells as APC can induce T cell tolerance (68)(69)(70)(71). In some reports, it has been shown that tolerance induction was mediated by upregulation of negative costimulatory molecules such as CTLA-4 and programmed cell death-1 on T cells (70,71). Our finding that the ppc1-5H MRLlpr mice have increased numbers of CTLA-4 + T cells suggest that the ppc1-5H NAA B cells may be able to deliver a tolerogenic signal to CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence that B cells as APC can induce T cell tolerance (68)(69)(70)(71). In some reports, it has been shown that tolerance induction was mediated by upregulation of negative costimulatory molecules such as CTLA-4 and programmed cell death-1 on T cells (70,71). Our finding that the ppc1-5H MRLlpr mice have increased numbers of CTLA-4 + T cells suggest that the ppc1-5H NAA B cells may be able to deliver a tolerogenic signal to CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although B cells can exhibit tolerogenic properties when stimulating naive T cells, little is known about in vivo reactivation of effector T cells by antigen-expressing naive B cells. [11][12][13][14] Clinical experience suggests cTCR ϩ T cells are diminished in the blood of patients with large antigen burdens, 4,15 but it is unclear to what extent this rapid clearance represents deletion or retention at antigen rich sites. Global lymphodepletion has been shown to increase T-cell survival, 16,17 but the effect of selective B-cell lymphodepletion before adoptive transfer of B-cell antigenspecific T cells has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to generate B cells with suppressive functions for use in cell therapy have mainly focused on either activating naive B cells with Ab to CD40 (20,21,28) or activating the cells with LPS or other TLR ligands and transducing the cells with retroviral vectors expressing relevant auto-Ags (16,19,29). In this study, we describe another approach through which Breg cells can be efficiently generated by simply incubating naive B cells with a relevant Ag conjugated to CTB for ca.…”
Section: Discussionmentioning
confidence: 99%